ANALISIS FAKTOR YANG MEMPENGARUHI POLA KONSUMSI RUMAH TANGGA MISKIN DI KECAMATAN KUBU, KABUPATEN KARANGASEM - Darmawati, Kadek Novi; Arka, Sudarsana (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.02.TAHUN.2024, 2024)
The aims of this study were 1) to analyze the effect of income, rice price, number of family members, and education simultaneously on the consumption pattern of poor households in Kubu District, Karangasem Regency. 2) to analyze the effect of income, rice price, number of family members, and education partially on the consumption pattern of poor households in Kubu District, Karangasem Regency. The sample size was calculated using the Slovin formula with a total of 99 poor household respondents based on the type of work. The method of determining the sample is simple random sampling based on the type of work of the head of the family, with the method of collecting observation data, in-depth interviews, and structured interviews using a questionnaire instrument. The data analysis technique used multiple linear regression analysis from the SPSS program. The results of the study simultaneously showed that income, rice price, number of family members, and education had a significant influence on the consumption pattern of RTM in Kubu District, Karangasem Regency. The results of the study partially show that income and education have a negative and significant effect on the consumption pattern of poor households in Kubu District, Karangasem Regency. The price of rice and the number of family members have a positive and significant impact on the consumption pattern of poor households in Kubu District, Karangasem Regency.